2020
DOI: 10.3390/molecules25225234
|View full text |Cite
|
Sign up to set email alerts
|

Co-Administration of Fendiline Hydrochloride Enhances Chemotherapeutic Efficacy of Cisplatin in Neuroblastoma Treatment

Abstract: Despite significant improvement of neuroblastoma (NB) patients’ survival due to recent treatment advancements in recent years, NB is still associated with high mortality rate. In search of novel strategies to increase NB’s susceptibility to pharmacological treatments, we investigated the in vitro and in vivo effects of fendiline hydrochloride as an enhancer of cisplatin antitumor activity. To assess the modulation of fendiline treatment on cisplatin responses, we used in vitro (evaluating NB cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Figure 1 reports the growth rate of tumor nodules and mice survival in the different experimental groups. Single treatments with acetazolamide or fendiline per se do not reduce tumor nodule growth, as shown by the daily recordings of nodule volume, which did not differ from DMSO-treated controls; cisplatin alone, at the dose used, had a moderate effect, but, in line with our previous results [7], the combined cisplatin/fendiline treatment reduced tumor growth much more effectively than low-dose cisplatin-based chemotherapy; conversely, no enhancing effects were observed in the co-treatment with cisplatin and acetazolamide, which induced an antitumor effect comparable to cisplatin alone. Interestingly, in the mice treated with the combination therapy which included all three molecules (Cis/Fen/Az), there was a reduced nodule growth rate equal to approximately one tenth of that observed in the vehicle-treated control mice, and if compared with the Cis/Fen treatment, the growth rate halved (Figure 1A,B).…”
Section: The Co-administration Of Acetazolamide With Cis/fen Therapy Increased the Mice's Survival And Inhibits Tumor Nodule Growthsupporting
confidence: 91%
See 4 more Smart Citations
“…Figure 1 reports the growth rate of tumor nodules and mice survival in the different experimental groups. Single treatments with acetazolamide or fendiline per se do not reduce tumor nodule growth, as shown by the daily recordings of nodule volume, which did not differ from DMSO-treated controls; cisplatin alone, at the dose used, had a moderate effect, but, in line with our previous results [7], the combined cisplatin/fendiline treatment reduced tumor growth much more effectively than low-dose cisplatin-based chemotherapy; conversely, no enhancing effects were observed in the co-treatment with cisplatin and acetazolamide, which induced an antitumor effect comparable to cisplatin alone. Interestingly, in the mice treated with the combination therapy which included all three molecules (Cis/Fen/Az), there was a reduced nodule growth rate equal to approximately one tenth of that observed in the vehicle-treated control mice, and if compared with the Cis/Fen treatment, the growth rate halved (Figure 1A,B).…”
Section: The Co-administration Of Acetazolamide With Cis/fen Therapy Increased the Mice's Survival And Inhibits Tumor Nodule Growthsupporting
confidence: 91%
“…It was also reported that fendiline, an L-type calcium blocker, causes cell death and reduction of proliferation and sensitization to cytotoxic drug activity of different tumor cell lines, through different mechanisms [40][41][42][43]. Among those, we recently identified a ncRNA named NDM29 whose stable overexpression is sufficient to induce neuronal differentiation of SKNBE2 NB cells preventing their tumorigenicity in vivo [6,7,9]. NDM29 acts mainly by downregulating the activity of ABC transporters thus increasing the susceptibility of NB cells to the effects of cisplatin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations